2019
DOI: 10.1007/s10964-018-0979-2
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization, Mood Symptoms, and Alcohol Use: Examining Effects among Diverse High School Youth

Abstract: Peer victimization is associated with alcohol use among adolescents. However, few studies have examined the mediating role of depression and anxiety, or differences by race. The current study examined the prospective relationship of peer victimization, depressive and anxiety symptoms, and alcohol use across two timeframes: 9 th to 11 th grade and 10 th to 12 th grade among African American and White youth. 2,202 high school youth (57.6% female) who identified as either African American (n=342, 15.2%) or White … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 66 publications
2
5
1
Order By: Relevance
“…Besides demonstrating strong evidence for temporal mediation effects, these latter results highlighted three important aspects of these mediations: they are general, immediately experienced and longer-lasting. These results are in line with previous studies for the internalizing path (Earnshaw et al, 2017;Marschall-lévesque et al, 2017;Rowe et al, 2019;Vannucci et al, 2020; . CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Besides demonstrating strong evidence for temporal mediation effects, these latter results highlighted three important aspects of these mediations: they are general, immediately experienced and longer-lasting. These results are in line with previous studies for the internalizing path (Earnshaw et al, 2017;Marschall-lévesque et al, 2017;Rowe et al, 2019;Vannucci et al, 2020; . CC-BY-NC-ND 4.0 International license available under a was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, structural equation modelling findings demonstrated that more frequent experiences of peer victimization in the 5th grade were associated with greater depressive symptoms in the 7th grade, which, in turn, were associated with a greater likelihood of alcohol use in the 10th grade (Earnshaw et al, 2017). In addition, Rowe et al (2019) found a significant mediation path between 10th grade peer victimization, 11th grade anxiety symptoms, and 12 th grade alcohol use (similar results were found for the 9 to 11 th grade path).…”
Section: Psychopathology As a Mediatorsupporting
confidence: 71%
See 1 more Smart Citation
“…Believing one's own characteristics or flaws caused victimization experiences might contribute to vulnerability to mental health problems. A recent study found that while anxiety and depression were significant mediators between peer victimization and alcohol use in White high school students, these indirect effects were not significant for African American students (Rowe, Zapolski, Hensel, Fisher, & Barnes-Najor, 2019). Further research is necessary to develop accurate and useful models of risk associated with peer victimization among racial and ethnic minority youth.…”
Section: Differential Consequences Of Bullying Involvementmentioning
confidence: 99%
“…A study recruiting African adolescents revealed a predominant indirect pathway between bullying and tobacco and alcohol use through the mediation of loneliness [33]. Another paper reported that the effect of peer victimization on alcohol use was mediated by depression and anxiety among white youths [34]. Two previous studies have indicated that depressive symptoms mediate the effect of bullying on substance use in females but not in males [35,36].…”
Section: Mediating the Effect Of Emotional Symptomsmentioning
confidence: 99%